Audio Visual Media to Improve the Ability to Read Daily Prayers in Early Childhood - Masitah, Yuflarti, Martini Jamaris, Jarudin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to improve reading daily prayers in kindergarten B children (ages 5-6) using audio-visual media. This study was conducted in RA Happy, Cipinang, East Jakarta. This study used the Jamaris &Edwita Martini model (modified model action research Model Kemmis and Mc Taggart), with procedures (1) Perform initial assessment (pre-assessment); (2) Planning; (3) Acting; (4) Observing; (5) Reflecting, and (6) final assessment. This study was conducted in 2 cycles, with seven meetings each cycle. Method interviews do data collection with teachers and school stakeholders as well as documentation. This study showed an improvement in reading daily prayers of children aged 5-6 years by using audio-visual media in terms of smoothness in the disclosure of prayer readings, the accuracy of sentence structure, and speech meaning. The increase was significant, namely pre-research data of 49.32% in cycle 1 to 66.47% or up by 17.15% and in the second cycle by 88.81% or up by 22.34%.